Hubungan Antara Asupan Energi dengan Status Gizi Mahasiswa Tingkat Akhir Fakultas Teknik Universitas Halu Oleo - Zahra, Az; Harleli, Harleli; Mochtar, Febriana (NHM PRESS, 2024)
Energy intake is derived from consuming macronutrients: energy adequacy and balance influence nutritional status. This quantitative research examined the correlation between energy intake and the nutritional status of final-year students at the Faculty of Engineering, Universitas Halu Oleo. Analytical observational method with a cross-sectional approach were employed to analyze the data obtained from 85 students who were sampled using the stratified random sampling. Energy intake data was collected through direct interviews using the semi-quantitative food frequency questionnaire (SQ-FFQ), as well as height and weight measurements. Bivariate analysis was conducted using the Spearman Rank correlation test with α = 0.05. The results showed that energy intake was positively associated with nutritional status (p=0.000, r=0.491). Based on the results of this research, students must ensure the adequacy of their nutrient intake to achieve ideal nutritional status.